1999
DOI: 10.1046/j.1365-2265.1999.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ras mutations in thyroid neoplasia

Abstract: Our data demonstrate a relatively low overall prevalence of ras mutations in thyroid neoplasia, with a predominance in follicular neoplasms. Their presence in follicular adenomas suggests that they may have an early aetiological role in the development of thyroid neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
3
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(139 citation statements)
references
References 19 publications
7
122
3
7
Order By: Relevance
“…These mutations are seen at different frequencies in different types of thyroid cancers. While in PTC, RAS mutations were observed in approximately 10% of cases, in ATC and FTC this frequency is 10-20% and 40-50%, respectively [90][91][92][93]. RAS mutation in PTC leads follicular variants, and also more encapsulation, and fewer metastases to lymph node [94,95].…”
Section: Rasmentioning
confidence: 98%
See 3 more Smart Citations
“…These mutations are seen at different frequencies in different types of thyroid cancers. While in PTC, RAS mutations were observed in approximately 10% of cases, in ATC and FTC this frequency is 10-20% and 40-50%, respectively [90][91][92][93]. RAS mutation in PTC leads follicular variants, and also more encapsulation, and fewer metastases to lymph node [94,95].…”
Section: Rasmentioning
confidence: 98%
“…However, codon 61 point mutations have been especially reported to cause tumor progression in an aggressive manner [98,99]. Studies with transgenic mice demonstrated that RAS mutations resulted in carcinogenesis and hyperplasia in thyroid [100].…”
Section: Rasmentioning
confidence: 99%
See 2 more Smart Citations
“…RAS mutations are strictly related to follicular architecture of DTC. First, they are detected in a wide portion (40-50%) of FTC (Lemoine et al 1989, Esapa et al 1999. Furthermore, among the 10-20% of PTCs harbouring the mutations, almost all cases are classified as follicular variant (Zhu et al 2003, Adeniran et al 2006.…”
Section: Ras Mutationsmentioning
confidence: 99%